A Biomimetic In Vitro Model of the Kidney Filtration Barrier Using Tissue‐Derived Glomerular Basement Membrane. Issue 16 (3rd July 2021) - Wang, Dan; Sant, Snehal; Ferrell, Nicholas
Abstract: The glomerular filtration barrier (GFB) filters the blood to remove toxins while retaining high molecular weight proteins in the circulation. The glomerular basement membrane (GBM) and podocytes, highly specialized epithelial cells, are critical components of the filtration barrier. The GBM serves as a physical barrier to passage of molecules into the filtrate. Podocytes adhere to the filtrate side of the GBM and further restrict passage of high molecular weight molecules into the filtrate. Here, a 3D cell culture model of the glomerular filtration barrier to evaluate the role of the GBM and podocytes in mediating molecular diffusion is developed. GBM is isolated from mammalian kidneys to recapitulate the composition and mechanics of the in vivo basement membrane. The GFB model exhibits molecular selectivity that is comparable to the in vivo filtration barrier. The GBM alone provides a stringent barrier to passage of albumin and Ficoll. Podocytes further restrict molecular diffusion. Damage to the GBM that is typical of diabetic kidney disease is simulated using hypochlorous acid and results in increased molecular diffusion. This system can serve as a platform to evaluate the effects of GBM damage, podocyte injury, and reciprocal effects of altered podocyte–GBM interactions on kidney microvascular permeability. Abstract : A biomimetic tissue culture model of the kidney filtration barrier is developed to evaluate molecular transport. The in vitro filtration barrier model employs kidney‐derived glomerular basement membrane to replicate the in vivo microenvironment. The filtration barrier model exhibits molecular selectivity and damage to the basement membrane increases molecular permeability.